Extreme binary black holes in a physical representation - Cabrera Munguia, Roberto Ivan (2018)
Stationary axisymmetric binary systems of unequal co- and counter-rotating extreme Kerr black holes separated by a conical singularity are studied. Both solutions are identified as two three- parametric subfamilies of the Kinnersley–Chitre metric, and fully depicted by Komar parameters: the two masses M1 and M2, and a coordinate distance R, where the angular momenta J1 and J2 are functions of these parameters. Our physical representation allows us to identify clearly some limits and novel physical properties.